Subconjunctival and topical application of recombinant tissue plasminogen activator in rabbits - Reggi, José Ricardo de Abreu; Hida, Richard Yudi; Hida, Milton Massato [UNESP]; Nishiwaki-Dantas, Maria Cristina; Suzuki, Hisashi (Conselho Brasileiro de Oftalmologia, 2015)
To quantify fibrin degradation products after topical and subconjunctival administration of recombinant tissue plasminogen activator in rabbits. Methods: Fibrin formation was induced in the anterior chamber in 25 rabbits. Subsequently, five rabbits received an injection of r-TPA (positive control) in the anterior chamber, another 10 received a subconjunctival injection of r-TPA, and the remaining 10 received instillations of topical r-TPA. Afterwards, samples of aqueous humor were collected and semi-quantitative analysis of fibrin degradation products (FDP) was performed. Results: No statistical differences were noted between the treatment and control groups at any time point. Fibrin degradation products semi-quantification showed statistical improvement in the control group and the subconjunctival group. Conclusion: Fibrin degradation products were observed in the anterior chamber after subconjunctival administration of r-TPA. However, it was probably not sufficient to cause fibrin degradation. Topical r-TPA did not effectively absorb anterior chamber fibrin.

Quantificar produtos de degradação de fibrina (PDF) após uso tópico e subconjunctival de ativador de plasminogênio tecidual recombinante (r-TPA) em coelhos. Métodos: Formação de fibrina foi induzida na câmara anterior em 25 coelhos. Cinco coelhos foram submetidos a injeção intracameral de r-TPA (controle positivo). Dez coelhos foram submetidos a injeção subconjuntival de r-TPA e dez coelhos foram submetidos a instilação tópica de r-TPA. Amostras de humor aquoso foram coletados e uma análise quantitativa dos produtos de degradação de fibrina foi realizada. Resultados: Não foi observado diferença estatisticamente significativa na degradação de fibrina em nenhum dos momentos estudados quando comparados com o controle. Porém foi observado diferença estatisticamente significante na quantificação do produtos de degradação de fibrina no grupo controle e no grupo subconjuntival. Conclusão: Produtos de degradação de fibrina foi observado nas amostras do grupo subconjunctival, porém, provavelmente não foi suficiente para degradar a fibrin presente. r-TPA tópico não foi efetivo em absorver fibrina na câmara anterior.
Uso tópico e subconjuntival de ativador de plasminogênio tecidual recombinante em coelhos
Keywords: Tissue plasminogen activator; Anterior chamber; Hyphema; Inflammation; Postoperative complications; Animals; Rabbits; Ativador de plasminogênio tecidual; Câmera anterior; Hifema; Complicações pós-operatórias; Animais; Coelhos